Recent Advances in Targetable Therapeutics in Metastatic Non-Squamous NSCLC - Bansal, Pranshu; Osman, Diaa; Gan, Gregory N.; Simon, George R.; Boumber, Yanis (Frontiers in Oncology, 2016)
Lung adenocarcinoma is the most common subtype of non-small cell lung cancer (NSCLC). With the discovery of epidermal growth factor receptor (EGFR) mutations, anaplastic lymphoma kinase (ALK) rearrangements and effective targeted therapies, therapeutic options are expanding for patients with lung adenocarcinoma. Here, we review novel therapies in non-squamous NSCLC, which are directed against oncogenic targets, including EGFR, ALK, ROS1, BRAF, MET, human epidermal growth factor receptor 2 (HER2), vascular endothelial growth factor receptor 2 (VEGFR2), RET and NTRK. With the rapidly evolving molecular testing and development of new targeted agents, our ability to further personalize therapy in non-squamous NSCLC is rapidly expanding.